DAMPAK PROYEK INFRASTRUKTUR STRATEGIS JALAN TOL TERHADAP PERTUMBUHAN WILAYAH HINTERLAND DI PROVINSI RIAU - Melani Noviantori Ramadhan; Bunga Putri Hendrika; B. Isyandi; Ufira Isbah; Dahlan Tampubolon (SINERGI : Jurnal Riset Ilmiah, 2026)
Transportation infrastructure development, particularly toll roads, plays an important role in promoting regional economic growth. This study aims to analyze the impact of the construction of the Pekanbaru–Dumai Toll Road and the Pekanbaru–Bangkinang Toll Road on the growth of hinterland regions in Siak Regency, Dumai City, and Kampar Regency based on Gross Regional Domestic Product (GRDP) at Constant Prices. The method used in this study is a descriptive method with a secondary data approach and trend analysis. The results show that the Pekanbaru–Dumai Toll Road has had a positive impact on economic growth through improved connectivity, distribution efficiency, and the strengthening of the trade and transportation sectors. Meanwhile, the Pekanbaru–Bangkinang Toll Road has shown relatively stable growth without significant changes. In general, toll road development has improved regional connectivity and supported economic growth, although the impact has not been evenly distributed and has been influenced by external factors such as the COVID-19 pandemic.